Quality of life and patient compliance with medical treatment after heart transplantation - Karagiannis, A.; Katsari, Vasiliki; Sarafis, Pavlos; Varaklioti, Agoritsa; Niakas, Dimitris; Domeyer, P. R. (My University, 2019)
OBJECTIVE To evaluate the quality of life (QoL) and compliance with prescribed treatment of patients following heart transplantation. METHOD The study population consisted of 65 patients who underwent heart transplantation during the last 15 years. The SF-36 Health Status Questionnaire was administered to assess QoL and the Morisky Medication Adherence Scale (MMAS) to record adherence to the prescribed medication regime. The data were analyzed using the Statistical Package for Social Sciences (SPSS), version 19.0. RESULTS Of the 65 patients, 53 (81.5%) were men, and their mean age was 48.2±13.1 years. The total SF-36 scale score was 67±8. No significant differences were found between the scores on the 8 scales of the SF-36 questionnaire and the age, gender, family status, and educational level of the patients (all p>0.05). The majority of patients 66.1% (n=43) showed a high degree of compliance with the prescribed treatment. No correlation was found between the MMAS score and scores on any of the 8 SF-36 scales or the total SF-36 score. CONCLUSIONS Heart transplant patients reported a satisfactory QoL after surgery and a high level of compliance with medication treatment. The further exploration of the QoL of patients undergoing heart transplantation and the understanding of its association with demographic characteristics may contribute to improvement in the health care and better support of patients after heart transplantation.
Keywords: Heart transplantation; Medical treatment; Patient compliance; Quality of life